Thermally Robust Solvent-Free Liquid Polyplexes for Heat-Shock Protection and Long-Term Room Temperature Storage of Therapeutic Nucleic Acids. - Chen,Y; Lin,X; Liu,X; Liu,Y; Bui-Le,L; Blakney,AK; Yeow,J; Zhu,Y; Stevens,MM; Shattock,RJ; Chen,R; Brogan,APS; et al. (Biomacromolecules, 2024)
Nucleic acid therapeutics have attracted recent attention as promising preventative solutions for a broad range of diseases. Nonviral delivery vectors, such as cationic polymers, improve the cellular uptake of nucleic acids without suffering the drawbacks of viral delivery vectors. However, these delivery systems are faced with a major challenge for worldwide deployment, as their poor thermal stability elicits the need for cold chain transportation. Here, we demonstrate a biomaterial strategy to drastically improve the thermal stability of DNA polyplexes. Importantly, we demonstrate long-term room temperature storage with a transfection efficiency maintained for at least 9 months. Additionally, extreme heat shock studies show retained luciferase expression after heat treatment at 70 °C. We therefore provide a proof of concept for a platform biotechnology that could provide long-term room temperature storage for temperature-sensitive nucleic acid therapeutics, eliminating the need for the cold chain, which in turn would reduce the cost of distributing life-saving therapeutics worldwide.